Decrease in air-sea CO2 fluxes caused by persistent marine heatwaves - Alexandre Mignot; Karina von Schuckmann; Peter Landschützer; Florent Gasparin; Simon van Gennip; Coralie Perruche; Julien Lamouroux; Tristan Amm (Nature Communications, 2022)
Ocean CO2 uptake at mid-latitudes counteracts CO2 release in the tropics, but we know little about the effects of marine heatwaves that modulate this process. Here, the authors use joint analysis of satellite measurements, in situ observation, reconstructions derived from machine learning algorithms, numerical model of the global ocean, and find that areas where PMHWs most frequently occur coincide with the regions that are the most critical for the oceanic carbon cycle.